Clinical Implications of Second and Third Trimester Surveillance Ultrasounds of Growth-Restricted Fetuses - Craig, Amanda M.; Kaur, Karampreet; Heerboth, Sarah A.; Chen, Heidi; Lauderdale, Chelsea J.; Shannon, Chevis; Zuckerwise, Lisa C. (American Journal of Perinatology Reports, 2021)
Objective We sought to investigate the positive predictive value of ultrasound-diagnosed fetal growth restriction (FGR) for estimating small for gestational age (SGA) at birth. Secondary objectives were to describe clinical interventions performed as a result of FGR diagnosis.Study Design This was a retrospective cohort of pregnancies diagnosed with FGR over 3 years at a single institution. Maternal demographics, antenatal and delivery data, and neonatal data were collected. Descriptive statistics and linear regression were conducted.Results We included 406 pregnancies with diagnosis of FGR in second or third trimester. Median birth weight percentile was 17 (interquartile range: 5–50) and only 35.0% of these fetuses were SGA at birth. The positive predictive value of a final growth ultrasound below the 10th percentile for SGA at birth was 56.9%. Patients averaged eight additional growth ultrasounds following FGR diagnosis. One hundred and fourteen (28.1%) received antenatal steroids prior to delivery, and 100% of those delivered after more than 7 days following administration. There were 6 fetal deaths and 14 neonatal deaths.Conclusion In the majority of cases, pregnancies diagnosed with FGR during screening ultrasounds resulted in normally grown neonates and term deliveries. These patients may be receiving unnecessary ultrasounds and premature courses of corticosteroids.
Keywords: fetal growth restriction; ultrasound; pregnancy; antenatal corticosteroids